Cognitive Stimulation at Home and in Child Care and Children's Preacademic Skills in Two‐Parent Families. Issue 5 (25th July 2020) - Cabrera, Natasha J.; Jeong Moon, Ui; Fagan, Jay; West, Jerry; Aldoney, Daniela
Abstract : This paper used the Early Childhood Longitudinal Study‐Birth Cohort ( N = 1, 258) to examine the influence of hilevels of cognitive stimulation from mothers, fathers, and childcare providers at 24 months and children's pre‐academic skills at 48 and 60 months in two parent families. Results from path analysis showed direct positive effects of fathers' early cognitive stimulation on early reading and math skills at 48 and 60 months. There were also two moderated effects: The effects of high levels of maternal stimulation at 24 months on early math and reading skills at 48 months were largest for children also receiving high levels of cognitive stimulation from their childcare providers. Implications for including fathers in studies of the home cognitive stimulation and strengthening the parent‐childcare connection are discussed.